Casos de ensino: dilemas, reflexões e conhecimentos de professores de Educação Física - Fabri, Eliane Isabel Julião (2021)
In the scenario of teacher education, narratives appear as adequate tools to access numerous aspects of teaching. The situations that occur in Physical Education classes express a diversity of elements that, when transformed into teaching cases, can help teachers to reflect on the dilemmas found in their pedagogical practices. Through the adoption of a constructive-collaborative research-intervention methodology, a continuing education initiative entitled “Teaching cases and the teaching in Physical Education” was developed. Ten Physical Education teachers belonging to the municipal and/or state network of the central-west region of São Paulo state participated in this study. Through the narratives, teaching cases, and records of the participants, this research aimed to identify and analyze the dilemmas, reflections, and knowledge related to the teaching of Physical Education teachers, based on the analysis and construction of teaching cases. The topics discussed referred to questions about gender, prejudice, exclusion, the beginning of the Physical Education teacher's career, and the organization of commemorative parties at school. Such topics are expressed as dilemmas present in the job execution of Physical Education teachers. Coping actions were proposed for all dilemmas, which involved teaching strategies, activities, research, movies, resources, joint actions, interdisciplinary actions, dynamics, debates, etc. Teachers' reflections were expressed through the analysis and production of teaching cases. The analysis of teaching cases revealed, mainly, the exploration of the pedagogical reasoning of the teachers who narrated how they think, plan and act in the face of several proposed situations. The knowledge expressed referred to specific knowledge, general pedagogical knowledge, and pedagogical knowledge of the content. The latter was the one that stood out most in the narratives of the teachers who, encouraged by the teaching cases, described and shared their ways of teaching, examples, strategies, and explanations. The production of teaching cases was realized as a powerful moment of reflection on the own practice of those who write and confirmed that this process involves emotional aspects that cannot be disregarded for working with teaching cases. The main contributions of the initiative “Teaching cases and the teaching in Physical Education” are related to the professional development of the participating teachers. Through teaching cases, they had the opportunity to externalize, register, share, and appropriate new pedagogical practices, as well as to recognize those they already knew. The initiative also contributed to the creation of spaces for exchanges and sharing of good teaching practices among peers.